Peculiarities of The Economic Crimes Committed with the Use of Information Technologies - Cherniavskyi, Serhii; Babanina, Viktoria; Vartyletska, Inna; Mykytchyk, Oleksandr (European Journal of Sustainable Development, 2021)
The article looks into peculiarities of the economic crimes committed using information technologies. Different approaches to the concept of the economic crime are analyzed to reveal types of economic crimes, which can be committed with the use of information technologies. It is stated that mostly two types of economic crimes could be committed using information technologies – online fraud and forgery. Subjects and objects of a forgery committed with the use of information technologies are analyzed. Close attention is paid to the online fraud and its specific features. The classification of types of the Internet fraud is made. Some specific characteristics of certain types of the Internet fraud are given in the article. Such types of the Internet fraud as spam, carding, phishing, fraud in online games are described. The main method used in the investigation is the method of comparative analysis, which was used to reveal differences between traditional economic crimes and economic crimes committed with the use if information technologies. The general conclusion was made that economic crimes committed with help of information technologies have a number of differences compared to traditional ones. These differences determine the features of the investigation of such crimes. In particular, such features are manifested in the implementation of operational and investigative measures and investigative actions.